THE ROLE OF E-COMMERCE IN CREATING CREATIVE AND INNOVATIVE MSME MANAGERS THROUGH TRAINING - Baby Poernomo; Avradya Mayagita (Adisam Publisher, 2026)
Empowering MSMEs is one of the national priorities considering their great potential and greatness in facing the economic crisis, helping to absorb labor, and as a motor of national economic growth. Therefore, MSMEs need to be managed by leaders who are creative and agile in all changes. This study aims to answer the question of how to implement